A Facile, Inexpensive and Scalable Route to Thiol-Protected α-Methyl Cysteine - Johnston, Heather J.; Hulme, Alison N. (Synlett, 2013)
A facile, scalable synthesis of α-methyl cysteine with three alternate thiol protecting groups (trityl, allyl and tert-butyl) is described. The thiol-protected amino acids are obtained in six steps from l-cysteine ethyl ester and are ideally suited for a range of natural product and solid-phase peptide synthesis applications.
Keywords: natural products; α-methyl cysteine; solid-phase peptide synthesis; camphorsultam auxiliary; P2-Et